Simultaneity of time and weather in 'exotic' climates: the experience of French writers in Africa and the Americas - SCOTT, DAVID (My University, 2012)
Foreign travel as affected by 'exotic' climates
PUBLISHED
(Journal) Special number: Temps et voyage
Keywords: travel, climate; Creative Arts Practice